Determinasi Pengungkapan Sharia Compliance Berdasarkan Standar AAOIFI Pada Bank Syariah Di Asia Tenggara - Dwi Kurniasari; Ahmad Tarmidzi Lubis; Mustafa Kamal (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2019)
This study aims to analyze the factors that influence disclosure level of sharia compliance based on AAOIFI standards. The dependent variable in this study is sharia compliance based on AAOIFI standard, while the independent variables are board age, board tenure, DPS educational bacground and firm age. This research is of a quantitative research, and the data used are secondary data. The samples are determined by purposive sampling method, which is as many as 6 Islamic banks in Southeast Asia. The observation period is from 2013 to 2017. The analysis methode used are content analysis to see the level of disclosure of sharia compliance based on AAOIFI and panel data regression analysis to examine the effect of independent variables on the dependent variable. Based on the results of panel data regression, the board age variables, board tenure, DPS educational background and firm age simultaneously influence AAOIFI shari'a compliance rates. However, partially only board tenure has a significant effect on the level of disclosure sharia compliance based on AAOIFI. Whereas, board age variables DPS educational background and firm age do not significantly influence AAOIFI disclosure sharia compliance rates.